2004
DOI: 10.1590/s0100-879x2004000300022
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oral tolerance and the effect of interleukin-4 on murine skin allograft rejection

Abstract: We studied the effect of oral and portal vein administration of alloantigens on mouse skin allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This result suggests that mucosal p277 peptide therapy can modify the dynamics of skin graft rejection in our models. Similar to our results, the use of different tolerization schedules with other antigens (donor cells, cytokines) employed in skin transplantation models has slightly increased the graft survival time (2–6 days over the control groups) [24, 25].…”
Section: Discussionsupporting
confidence: 85%
“…This result suggests that mucosal p277 peptide therapy can modify the dynamics of skin graft rejection in our models. Similar to our results, the use of different tolerization schedules with other antigens (donor cells, cytokines) employed in skin transplantation models has slightly increased the graft survival time (2–6 days over the control groups) [24, 25].…”
Section: Discussionsupporting
confidence: 85%
“…Some experimental transplantation studies 20,21 have described oral administration of spleen cells along with the transplanted tissue in order to reduce the rejection, as well as the amount of immunosuppressive agents being used. This makes it possible to justify the evolution of better lipid profile in Group 4.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…More recently, Wilkes' group reported that tolerance against fully-mismatched lung allografts could be achieved using a self-protein, collagen type V (col-V) (114). Administration of donor antigens has also been found to be effective using intragastric (115), intra-jejunal (116), transrectal, and intratracheal routes (107). The tolerance induced using such transmucosal routes has been shown to be T cell dependant as T cells, but not serum, from tolerized recipients could transfer tolerance.…”
Section: Extra-thymic Inoculation Of Allopeptidesmentioning
confidence: 99%